2017
DOI: 10.1021/acssuschemeng.6b02884
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach to Prepare Ultrathin Lignocellulosic Film for Monitoring Enzymatic Hydrolysis Process by Quartz Crystal Microbalance

Abstract: The applications of quartz crystal microbalance (QCM) rely heavily on the preparation of ultrathin films. So far, techniques on direct lignocellulosic film making without components isolation have been hardly investigated. In this work, a novel approach was developed to prepare spin-coated ultrathin films based on the complete dissolution of ball-milled wood in LiCl/DMSO solvent system. The surface analysis and elemental composition of the films respectively using atomic force microscopy and X-ray photoelectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Lignin films were prepared on gold-coated QCM sensors (QSX301, Västra Frölunda, Sweden) as previously described [ 35 ]. Prior to film preparation, QCM gold sensors were cleaned via treatment with 25% ammonia solution/30% hydrogen peroxide/water (1:1:5, v/v/v) at 75 °C for 5 min, rinsed with deionized water, and finally dried under nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignin films were prepared on gold-coated QCM sensors (QSX301, Västra Frölunda, Sweden) as previously described [ 35 ]. Prior to film preparation, QCM gold sensors were cleaned via treatment with 25% ammonia solution/30% hydrogen peroxide/water (1:1:5, v/v/v) at 75 °C for 5 min, rinsed with deionized water, and finally dried under nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…The morphology and roughness of the lignin films were characterized by atomic force microscopy (AFM) (Dimesion Edge, Brucker, Saarbrücken, Germany). The images were scanned in tapping mode, and analyzed using NanoScope analysis software according to a previous report [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The dynamics of enzymatic hydrolysis showed that when pseudo-lignin and residual lignin were mixed with cellulose, the maximum glucose release was reduced and the time to reach the maximum enzymatic hydrolysis efficiency was longer than that of pure cellulose. Jiang et al [ 165 ] prepared a full-component lignocellulose ultrathin film using the LiCl/DMSO solvent system. The in situ enzymatic hydrolysis of the film in QCM-D verified the non-productive adsorption of cellulase onto lignin.…”
Section: Interaction Between Lignin and Cellulasementioning
confidence: 99%
“…Dry Masson pine was milled in a planetary ball mill (Fritsch Pulverisette 7, Idar-Oberstein, Germany) at 40 °C as described previously [34]. The milled Masson pine was dispersed in a dioxane/water (96/4, v/v) mixture in a 1:25 ratio of wood to solvent and mechanically stirred.…”
Section: Methodsmentioning
confidence: 99%
“…The enzyme adsorption/desorption behaviors on lignin films were monitored in situ using quartz crystal microgravimetry with dissipation monitoring (QCM-D) (QCM-D E4 model, Biolin Corp., Gothenburg, Sweden) at 4 °C as previously described [34]. The purified MMPL was dissolved in dioxane at a concentration of 1% (w/v).…”
Section: Methodsmentioning
confidence: 99%